2020
DOI: 10.1038/s41598-020-72340-9
|View full text |Cite
|
Sign up to set email alerts
|

The anti-apoptotic Coxiella burnetii effector protein AnkG is a strain specific virulence factor

Abstract: The ability to inhibit host cell apoptosis is important for the intracellular replication of the obligate intracellular pathogen Coxiella burnetii, as it allows the completion of the lengthy bacterial replication cycle. Effector proteins injected into the host cell by the C. burnetii type IVB secretion system (T4BSS) are required for the inhibition of host cell apoptosis. AnkG is one of these anti-apoptotic effector proteins. The inhibitory effect of AnkG requires its nuclear localization, which depends on p32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 60 publications
3
25
0
Order By: Relevance
“…After confirming efficient elimination of CDK9 by THAL ( Fig 8B ), we analyzed whether the presence or absence of CDK9 influences the activity of GFP-AnkG 1-28 . While GFP-AnkG 1-28 expression protected the cells from staurosporine-induced apoptosis, as shown before [ 17 ], it did not protect from THAL-induced apoptosis ( Fig 8C ). Treatment with both, staurosporine and THAL, increased the rate of apoptotic cells.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…After confirming efficient elimination of CDK9 by THAL ( Fig 8B ), we analyzed whether the presence or absence of CDK9 influences the activity of GFP-AnkG 1-28 . While GFP-AnkG 1-28 expression protected the cells from staurosporine-induced apoptosis, as shown before [ 17 ], it did not protect from THAL-induced apoptosis ( Fig 8C ). Treatment with both, staurosporine and THAL, increased the rate of apoptotic cells.…”
Section: Resultssupporting
confidence: 83%
“…To get a first impression whether the interaction of AnkG with DDX21 might be important for the anti-apoptotic activity of AnkG, we asked which parts of AnkG might interact with DDX21. We have previously shown that the N-terminal region of AnkG, comprising amino acids 1–28, is necessary and sufficient for anti-apoptotic activity and exclusively localizes in the host cell nucleus, while the region from amino acids 70–338 did not prevent cell death and has a cytoplasmic localization [ 14 , 15 , 17 ]. As shown in Fig 2B , HA-tagged DDX21 was bound by GFP-AnkG 1-28 and GFP-AnkG 1-69 , but not by GFP-AnkG 70-338 , indicating that DDX21 binds to the anti-apoptotic region of AnkG.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been seen that the amino terminal 1–69 region codify a domain that is both necessary and sufficient to interact with p32 and to inhibit the apoptosis, whereas truncated variants are not able to block apoptosis. Moreover, to prevent pathogen-induced cell death, AnkG needs to be localized in the nucleus ( Eckart et al., 2014 ; Schäfer et al., 2017 ; Schäfer et al., 2020 ).…”
Section: Apoptosis and Inflammasome In Coxiella Burnetii Infectionsmentioning
confidence: 99%
“…CvpB binds to phosphatidylinositol 3-phosphate to enhance association of the autophagosomal components to the CCV ( Martinez et al., 2016 ). Another effector, AnkG plays a key role in anti-apoptosis, which is distinct from maturation of the CCV, though it is important in progression of disease in a Galleria mellonella infection model ( Schafer et al., 2020 ). NopA is injected into host cells and impacts the innate immune response to Coxiella infection, but does not impact trafficking of this pathogen to a replicative CCV ( Burette et al., 2020 ).…”
Section: The Lysosomal-like Coxiella -Containing Vacuolementioning
confidence: 99%